If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 50 + -3x + -5 = 3x + 24 + x Reorder the terms: 50 + -5 + -3x = 3x + 24 + x Combine like terms: 50 + -5 = 45 45 + -3x = 3x + 24 + x Reorder the terms: 45 + -3x = 24 + 3x + x Combine like terms: 3x + x = 4x 45 + -3x = 24 + 4x Solving 45 + -3x = 24 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 45 + -3x + -4x = 24 + 4x + -4x Combine like terms: -3x + -4x = -7x 45 + -7x = 24 + 4x + -4x Combine like terms: 4x + -4x = 0 45 + -7x = 24 + 0 45 + -7x = 24 Add '-45' to each side of the equation. 45 + -45 + -7x = 24 + -45 Combine like terms: 45 + -45 = 0 0 + -7x = 24 + -45 -7x = 24 + -45 Combine like terms: 24 + -45 = -21 -7x = -21 Divide each side by '-7'. x = 3 Simplifying x = 3
| 3x/2=9/3 | | k^2-28k-13=0 | | c+2d-8+2c=4d+10 | | 9h-3=84 | | v^2-4v-25=0 | | 36=.5*(x+6)-(3x-2) | | -9(v-3)=9v+9 | | (50*25i)/(50-25i) | | -5-(r+5)=-28-4r | | 5x+2x-9x=4 | | -4(2x+-5)=4 | | x^2-2xy+4=0 | | X^2-6x=x-6 | | 5d+1-2d=-3c | | x^2-10x-y^2-6y+16=0 | | 6x-14=-3x+22 | | -1(7x-1)=-6 | | 15x-20=3x+4 | | 3n+7=7(1+8n) | | 3/7j-1/7=3/14 | | 49=-7/8y | | (3z-2)2=4 | | 10y-8y=-12 | | (m-2m^2)/(-m)-3m | | 5d-4c=7d+16 | | X+22=10x+4 | | x/y=5,3 | | (2x-6)*(x+1)=10 | | 25=2.5x | | x(3)=216 | | 10t+5t-1=130 | | 4x-3(-5-3x)=6x-34 |